Abu Muslim qala: an iron-production site along Central Asia's medieval north–south trade routes. (October 2021) - Brite, Elizabeth Baker; Fletcher, Emily; Cooper, H. Kory; Amirov, Shamil; Iskanderova, Aysulu; Toreniyazov, Azizkhan; Kidd, Fiona J.; Khozhaniyazov, Gairadin
Abstract: Abstract : Archaeological remains at a religious site dedicated to a Yasawiyya Sufi saint reveal a possible centre of iron production along the trade routes connecting the medieval urban centres of Central Asia.